Approaches to fighting corruption and managing integrity in Malaysia: a critical perspective / Noore Alam Siddiquee - Siddiquee, Noore Alam (2010)
The Government of Malaysia has made continuous efforts and put in place an elaborate set of strategies and institutions aimed at combating corruption and promoting integrity in the society. The nation’s anti-corruption drive received a major boost in 2003 when Abdullah Ahmad Badawi took over as Malaysia's fifth prime minister. Soon after its take over of power the new government declared containing corruption as its main priority which was followed by a series of concrete measures. However, the governmental attempts and strategies in Malaysia appear to have met with little success, as evidenced by the current data that suggests entrenched corruption in the society. Evidence shows that despite governmental campaigns and initiatives, corruption has remained acute, widespread and, in fact, worsened in recent years. This paper presents a critical overview of the anti-corruption strategies being followed in Malaysia and explores some of the problems and limitations of the current approach to fighting corruption and managing integrity in the society.